Game Simulasi Aman Berkendara Roda Dua di Jalan Umum - Godham Eko Saputro (Ars: Jurnal Seni Rupa dan Desain, 2012)
The number of accidents on the streets hasalways been dominated by motorcycles. Treefactors that cause these accidents are humanerrors, vehicles and environments. Te highestfactor causing the accident is human error. Itoften triggers accidents. Riding their motorcycles,riders struggle to get to their destination as soon aspossible. Tis often leads to accidents. To reduce theaccident number, the solution oﬀered is creating agame application to complete the already existingbooks and theories providing trafc guidance andalso the counseling given by the authorities. It isin the form of safety riding simulation game thatis designed as closely as possible with good drivingtechniques. Advantageous tips and tricks completethe game. A PC tablet with Android operatingsystem with maximal multimedia features is usedto guarantee that the users will feel the sensation ofthe simulation.